RECONSTRUCTION OF EXECUTIVE AND LEGISLATIVE AUTHORITIES TO MAKE A GOOD GOVERNANCE BASED ON WELFARE VALUES - muhammad khamim (UNISSULA, 2017)
The executive and legislative powers of good governance based on welfare values imply that the executive and legislative bodies as the state organizers and the bearers of the mandate to manage public affairs should prioritize the general interests and safeguard the public good over many individual and group interests. The executive and legislative authorities in realizing good governance have not worked well due to the practice of extraterrestrial partnership relations, especially in terms of APBD (Regional Budget) arrangements that seem to promote personal or group interests. The role of function is large enough to cause conflict between the executive and legislative (local government), especially the head of the region.